Critique of Arab Reason; Epistemology of Islamic Awakening - Achmad Tijani (Al-Albab, 2019)
Abdul Mukti Rouf, Kritik Nalar Arab: Muhhamad ‘Abid Al-Jabiri, Yogyakarta: LKiS, 2018Reading the book Critique of Arab Reason of Muhammad Abid Aljabiri from the writings of Abdul Mukti Ro'uf requires sufficient intellectual energy. This book is classified as fairly serious research. Its material objects that touch the historical and philosophical aspects that are integrated together make the reader trapped and faced with the arguments of the great figures of the Islamic world with various dynamics that take place in it. Perhaps the involvement of the great figures of the Islamic world is an inevitable choice. Even not only the great figures of internal Islamic community, but a number of large external figures who concentrate in Islamic studies are also involved to present sharp analysis with sufficient weight in breaking down Al-Jabiri's great thought.